Keteladanan Guru Sebagai Cara Internalisasi Pendidikan Karakter Disiplin dan Tanggung Jawab di SMP Wahid Hasyim Sumberwudi - Eva Nur Aini Maghfiroh; Mahbub Junaidi; Khotimatus Sholikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the role of teacher role models in internalizing the values ​​of character education of discipline and responsibility to students at SMP Wahid Hasyim Sumberwudi. The approach used is descriptive qualitative with data collection methods through in-depth interviews, direct observation, and documentation. The subjects of the study included the principal and teachers. The results of the study indicate that teacher role models are a key factor in shaping students' character. Teachers not only convey the values ​​of discipline and responsibility verbally, but also provide concrete examples in everyday life in the school environment. Internalization of these values ​​takes place through routine interactions between teachers and students, consistent application of rules, and positive behavioral habits. This study concludes that teacher role models have a significant influence in shaping students' character of discipline and responsibility, so it is important for schools to continue to encourage a culture of role models as part of a character education strategy.